Anesthetic Outcomes of Children With Arthrogryposis Syndromes: No Evidence of Hyperthermia. (March 2017) - Gleich, Stephen J.; Tien, Michael; Schroeder, Darrell R.; Hanson, Andrew C.; Flick, Randall; Nemergut, Michael E.
Abstract : BACKGROUND: Arthrogryposis syndromes are a heterogeneous group of disorders characterized by congenital joint contractures often requiring multiple surgeries during childhood to address skeletal and visceral abnormalities. Previous reports suggest that these children have increased perioperative risk, including hypermetabolic events discrete from malignant hyperthermia, difficult airway management, isolated hyperthermia, and difficult IV line placement. We sought to compare children with arthrogryposis multiplex congenita (AMC) versus the less severe, distal arthrogryposis syndromes (DAS) and to evaluate possible intraoperative hyperthermia of patients with AMC. We hypothesized that children with AMC had a greater incidence of intraoperative hyperthermia and more difficulty with airway management and IV access. METHODS: Children aged 0 to 25 years with arthrogryposis syndromes who underwent anesthesia from 1972 to 2013 were identified. The medical records were reviewed for demographics, arthrogryposis type, and anesthetic complications. AMC subjects were compared with DAS subjects. To evaluate the probability of hyperthermia and hypermetabolic responses of patients with AMC, we performed a post hoc case–control analysis. Patients with AMC were matched in a 1:2 ratio to patients without arthrogryposis to evaluate the primary outcome of maximum intraoperative temperature. RESULTS: Forty-five patients with AMC and 16 patients with DAS underwent 264 and 105 unique anesthetics, respectively. There was no significant difference in intraoperative hyperthermia or hypermetabolic events (odds ratio [OR], 0.94; 95% confidence interval [CI], 0.36–2.47; P = .90). Children with AMC were more likely to have difficult IV access (OR, 7.1; 95% CI, 1.81–27.90; P = .005). Additional evidence suggested that difficult airway management (OR, 4.06; 95% CI, 1.01–16.39; P = .049) and hemodynamic instability (OR, 4.22; 95% CI, 1.03–17.26; P = .045) were more likely in children with AMC. From post hoc case–control analysis, there was no significant difference in the mean maximum intraoperative temperature (estimated difference +0.04°C; 95% CI, −0.14 to +0.22; P = .64) or odds of intraoperative hyperthermia (OR, 1.49; 95% CI, 0.78–2.82; P = .223) for patients with AMC compared with control subjects. CONCLUSIONS: Children with arthrogryposis syndromes present challenges to the anesthesia and surgical teams, including greater neuromuscular disease burden and challenging peripheral IV placement, with additional evidence suggesting difficult airway management and intraoperative hemodynamic instability. Although more definitive studies are warranted, we did not find evidence of increased odds of intraoperative hyperthermia or hypermetabolic responses.